2000
DOI: 10.1046/j.1365-2168.2000.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative portal vein embolization improves prognosis after right hepatectomy for hepatocellular carcinoma in patients with impaired hepatic function

Abstract: Preoperative PTPE improves the prognosis after right hepatectomy for HCC in patients with impaired hepatic function, although it does not prevent tumour recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 11 publications
2
80
0
1
Order By: Relevance
“…Our present results showed that changes in hepatic volumes did not differ significantly between normal and impaired liver, although changes of liver volume tended to be lower in liver cirrhosis. Therefore, PVE can be applied for even patients with diseased liver as previously reported [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Our present results showed that changes in hepatic volumes did not differ significantly between normal and impaired liver, although changes of liver volume tended to be lower in liver cirrhosis. Therefore, PVE can be applied for even patients with diseased liver as previously reported [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…27,209 Chemoembolization of the tumor prior to resection offers no benefit. 210 The same is true for the general use of portal vein embolization of the hepatic lobe hosting the tumor 211,212 to induce compensatory liver growth and functional capacity in the non-affected lobe prior to a major resection. It has also been suggested that malignant hepatocytes may also respond to the proliferative stimulus and this could result in uncontrolled tumor progression.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…However, Wu et al found effective preoperative TACE might be one of the best methods for resectable HCCs including small HCCs for improving disease-free survival after hepatectomy [74] . Preoperative portal vein embolization could improve prognosis after right hepatectomy for HCC in patients with impaired hepatic function, but cannot prevent tumor recurrence after HCC resection [75] . Main portal branch transection combined with major liver resection and neoadjuvant and adjuvant locoregional immunochemotherapy could increase the resectability rate and the overall survival and DFS [76] .…”
Section: Preoperative Adjuvant Therapy (Neoadjuvant Therapy)mentioning
confidence: 99%